L. plantarum WCFS1 enhances Treg frequencies by activating DCs even in absence of sampling of bacteria in the Peyer Patches - Bermudez-Brito, Miriam; Borghuis, Theo; Daniel, Catherine; Pot, Bruno; de Haan, Bart J.; Faas, Marijke M.; de Vos, Paul (Scientific reports, 2018)
Probiotics such as L . plantarum WCFS1 can modulate immune responses in healthy subjects but how this occurs is still largely unknown. Immune-sampling in the Peyer Patches has been suggested to be one of the mechanisms. Here we studied the systemic and intestinal immune effects in combination with a trafficking study through the intestine of a well-established immunomodulating probiotic, i.e. L . plantarum WCFS1. We demonstrate that not more than 2–3 bacteria were sampled and in many animals not any bacterium could be found in the PP. Despite this, L . plantarum was associated with a strong increase in infiltration of regulatory CD103 + DCs and generation of regulatory T cells in the spleen. Also, a reduced splenic T helper cell cytokine response was observed after ex vivo restimulation. L . plantarum enhanced Treg cells and attenuated the T helper 2 response in healthy mice. We demonstrate that, in healthy mice, immune sampling is a rare phenomenon and not required for immunomodulation. Also in absence of any sampling immune activation was found illustrating that host-microbe interaction on the Peyer Patches was enough to induce immunomodulation of DCs and T-cells.